PERAN SENTRAL PEMUDA HINDU DALAM PERUBAHAN SOSIAL MENUJU REVOLUSI INDUSTRI 4.0 (Perspektif Sosio – Normatif Moralistik dan Pedagogi) - I Gede Agus Siswadi; I Dewa Ayu Puspadewi (UHN IGB Sugriwa Denpasar, 2022)
The presence of a superior young generation is highly expected by a nation. Because the progress of a nation will be seen how the role of youth in various fields, including in the fields of science, technology and education. Youth in this case is the determinant of the development to the advancement of a civilization, so it can be said that the role of youth is very central. The progress of a nation if the character and morals of its youth are superior, with this they will be better able to face challenges and changes towards the industrial revolution 4.0. This article seeks to present the role of youth in facing the industrial revolution 4.0. By using the descriptive method, it can be seen that the role of youth in social change and as agents of social change is important because it is youth who will hold the baton from dynamic socio-cultural behavior. In preparing the golden generation (Golden Age) Hindu youth must be literate towards education and issues that develop in the world of education. With education, character will be constructed with noble and superior values ​​for Hindu youth.